Preaching Environmental Jurisprudence: Reviving the Concepts of Ihya Al-Mawat and Hima in Tangible Actions - Adnan, Mohammad; Husein, Sajjad (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
This article explores the integration of classical Islamic legal concepts, specifically Ihya Al-Mawat (reviving dead land) and Hima (protected zones), into contemporary preaching (dawah) as a form of applied Environmental Jurisprudence. The central argument posits that dawah must transcend verbal discourse and manifest in tangible action to address the global ecological crisis. Through textual analysis and case studies, this article demonstrates how these two jurisprudential concepts—traditionally associated with land ownership and conservation—can be revitalized and adapted to modern contexts such as ecosystem restoration, urban greening, community-based conservation, and sustainability policy advocacy. The article emphasizes that a preaching approach based on Fiqh al-Bi'ah (environmental jurisprudence) is not only theologically relevant but also serves as a strategic instrument for actualizing the principles of khilafah (stewardship) and maslahah (public welfare). Practical applications of these concepts are evidenced in initiatives like "Green Mosques," forest waqf (endowment) programs, and the integration of environmental fatwas with modern science. In conclusion, reviving Ihya Al-Mawat and Hima through transformative dawah represents an urgent religious calling to build an ecological consciousness with concrete impact, while strengthening the role of Muslim communities in the global environmental justice movement.